(untitled) (Research, Society and Development, 2021)
The decline in bee communities in recent years has been a major concern worldwide. The increase in the mortality of these pollinators is related to several factors, the main one being the intensive use of pesticides in agricultural crops. Brazil is the world leader in use of pesticides since 2008 and recent changes in legislation have facilitated the commercialization of certain pesticides whose marketing has been banned in several countries. This review addresses how current Brazilian legislation on agrochemicals has influenced the increase in bee mortality. Under the current federal government, in 2019 and 2020, 474 and 493 new pesticides were registered in the country, respectively, some of them classified as highly toxic to bees. In addition, public policies in Brazil led by certain sectors of agribusiness have also contributed to increase the number of threats and the mortality of bees, making it difficult for the beekeeping sector to act in opposition. Understanding how these policies directly affect pollinator conservation allows decision-making to help mitigate their environmental and economic impacts in Brazil. Otherwise, without effective actions to mitigate the abusive use of pesticides, the numerous studies demonstrating its direct impacts on the bee’s survival will be of no use.